(3eLehYI aj GdgfOSIs - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3ebGdI dGHf GdgjKe ai bSeI GdNW GdPi GSJYedg CQTejOS ai GdebGdI GdKGfjI bGd GQTejOS GSJYed ai GdTcd GdQGHY ef GdebGdI GdKGfIj ai GdcQI hGdCSWhGfI NWkG aQVI s
(3BNQgG (B:s
(3cfSHI eQHY H A Edi eQHY A M hPdc eG CQOfGg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY YTQs
(3HgG CTcGd gfOSjI Jdjg aGFOI dCHi GdbGSe Ydi GdSeSGWis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs